THE EFFECT OF MOTIVATION ON EMPLOYEE JOB SATISFACTION IN THE OFFICE OF THE DISTRICT HEAD OF KOTA TIMUR, GORONTALO PROVINCE - Cayati, Evi Nurfila; Latif, Samin; Musa, Maman (Jurnal Ilmu Manajemen dan Bisnis, 2024)
This study aims to determine the effect of motivation on employee job satisfaction at the East City Sub-District Office of Gorontalo Province. This type of research uses quantitative methods with a correlational approach. The population and sample in this study were all employees totaling 30 employees in the East City Sub-District Office of Gorontalo Province. Data collection techniques using observation, questionnaire (questionnaire). Data analysis method using simple linear regression. The results showed that motivation (X) had a significant effect on employee job satisfaction (Y) with the results of t count 4,981 with a significance level of 0,00 <0.05. From the processed data, the sig value is 0.000 with a probability value of 0.05. Because the sig value <0.05 so motivation (X) has a significant effect on employee job satisfaction (Y)